SWOT Analysis of the Development Event Promotion at Pavilion Batur, Geopark, Bangli Regency, Bali - Suwintari, I Gusti Ayu Eka; Dewi, I Gusti Ayu Melistyari (Stupa, 2020)
Since the operation of the UNESCO Global Geopark (BUGG) Batur Management Agency has had a positive impact in increasing the Regional Original Revenue (PAD) of the Regency of Bangli, it hasn't even been a year in operation since 2019 the revenue achieved has almost reached half of the target. The development of the campaign carried Museum Geopark Batur Kintamani is not maximized in terms of the management of events that can be done there, based on the phenomenon, the focus of this study is to determine the appropriate strategies with potential tourist attraction that can then be implemented by the local community and become one alternative forms of tourism in Bangli Regency and North Bali in general. This research using qualitative and quantitative data. While the primary data used are documents obtained from the internet. Data collection in this study uses the method of observation and documentation. The strategy that can be used in developing the Batur Kintamani Geopark Museum is by utilizing all the potential it has, starting from creating an event to introduce this geopark, making tour packages that include other tourist objects around the geopark, and capturing potential markets, especially among students. To minimize weaknesses, geopark managers can learn more knowledge and skills on how to maximize the potential of the Batur Kintamani Geopark Museum.